Structural optimization of composite corrugated cores with variable stiffness - Shamsi Monsef, Mohammad Sajad; Shaban, Mahdi; Khoshlesan, Sanaz (Mechanics based design of structures and machines, 2024)
Outstanding progress in manufacturing technology of fiber-reinforced composite materials, allows designers to go beyond classical design rules. Composites with variable stiffness are an innovative division of composite materials that provide more efficient designs for engineers due to their diverse design parameters. In this study, a straightforward methodology is presented for the design of sandwich panels with corrugated variable stiffness core. Based on the homogenization method, a unit-cell of the sandwich panel is used as a representative volume element for the sandwich panel with corrugated core. Due to multiple design variables, conventional numerical and analytical methods cannot be applied to variable stiffness composites, thus PYTHON/ABAQUS framework is developed to determine the extensional and bending behavior of unit-cells. Details of this framework including PYTHON scripting and ABAQUS finite element solver are given along with their corresponding functions. Furthermore, the elitist genetic algorithm is incorporated into a framework for the optimum design of variable stiffness cores. Two optimization problems, namely composites with variable thickness and variable angle are considered for unit-cells, and associated constraints, boundary conditions, and fitness functions are discussed in detail. In addition to the benefits of the proposed framework, the obtained results reveal notable enhancement in the extensional and bending behavior of unit-cell. Results reveal that corresponding displacements are significantly improved (up to 80%) when using the optimum variable thickness case. For variable angle cases, the improvement of displacements is up to about 28%.